Outdoor Study for Social Studies to Strengthen Pancasila Student Profile: Learning Objectives and Challenges - Ratna Anggraeni; Tri Marhaeni Pudji Astuti; Cahyo Budi Utomo (International Journal of Education and Humanities, 2024)
This research topic is social studies learning through outdoor study as a form of implementing the Merdeka curriculum by utilizing the tourist village around SMP N 3 Satu Roof Undaan, Kudus. Social studies teachers use the theme of local wisdom in the project to strengthen the profile of Pancasila students (P5) so that students can carry out more innovative and exploratory learning activities. The aim is to analyze the flow of learning objectives (ATP) owned by social studies teachers, analyze outdoor studies through tourist villages, and analyze the obstacles faced when implementing the outdoor study. This type of research is qualitative and refers to primary and secondary data. Research sources from informants, document studies, and data collection techniques include interviews, observations, documents, and focus group discussions (FGD). The results of this research, the social studies teacher at SMP N 3 Satu Atap Undaan created and implemented a flow of learning objectives (ATP) based on learning outcomes (CP) that the government had determined. The first outdoor study carried out by class VII students explored the traditional market "Sarwono" using the PEKARTI teaching method. The barriers in this research are educational barriers (Q1), student barriers (Q2), school barriers (Q3), and other barriers (Q4)